Enhancement of Antibody Responses in Chickens Vaccinated with a Plasmid DNA Construct of Avian Influenza Virus H5 Gene Infused with Hsp70 of Mycobacterium Tuberculosis - Pirozyan, Mehdi Rasoli (2009)
Currently, this region is battling against highly pathogenic avian influenza (HPAI) virus H5N1 and the virus has been isolated in non-poultry birds in various countries in Middle East as well as in the European and African continents. These developments have ignited global fears of an imminent influenza pandemic. The adoption of a vaccination policy, targeted either to control or to prevent infection in poultry, is generally discouraged. Nevertheless, the need to boost eradication efforts in order to limit further spread of infection and avoid heavy economic losses, and advances in modern vaccine technologies, have prompted a re-evaluation of the potential use of vaccination in poultry as an additional tool in comprehensive disease control strategies. Hence, several types of vaccines are available and some of them have been tested experimentally and/or used in commercial farms. DNA vaccines have been shown to be an effective approach to induce antigen-specific cellular and humoral immunity. However, the low immune intensity in clinical trials limits the application of DNA vaccines. Heat shock proteins (HSPs) or stress proteins are highly conserved molecules that act as chaperons. Among the HSPs, HSP70 family is well characterized protein that showed potent adjuvant effects on the innate and adaptive immune responses. In this study, we developed DNA vaccine based on H5 gene, and enhanced the DNA vaccine potency with Mycobacterium tuberculosis heat shock proteins 70 (HSP70) as adjuvant. Hence, a series of DNA plasmids encoding H5 and NP from Malaysian H5N1 (A/Ck/Malaysia/5858/2004) were constructed and then fused with HSP70. The H5, NP, H5-HSP70 and NP-HSP70 recombinant proteins were expressed in Vero cells. We further investigated the ability of the pcDNA3.1/H5 and pcDNA3.1/H5-HSP70 constructs in inducing H5 specific antibody responses in SPF chickens. pcDNA3.1/H5 and pcDNA3.1/H5-HSP70 were administered to 10 days old SPF chickens in three doses of 100 μg by the intramuscular route, two weeks apart. Chickens were bled every week and H5 specific antibody was measured using hemagglutination inhibition (HI) test. The ability of the constructed plasmids in inducing the expression of H5 and H5-HSP70, respectively, in chickens was examined by RT-PCR. In vivo expression was confirmed based on detection of H5 RNA transcripts in muscle and spleen of chickens inoculated with the constructed DNA vaccines. The HI test was carried out using H5 antigen from a low pathogenic avian influenza virus (LPAIV), A/Duck/Malaysia/8443/2004 (H5N2). Sequence analysis of H5 genes of H5N1 and H5N2, respectively, that was used in this study showed nucleotide and amino acid identity of more than 87%. In addition, all the chickens immunized with pcDNA3.1/H5 and pcDNA3.1/H5-HSP70 showed HI titer in week three after the first immunization. The HI titer was more prominent from first booster onwards in the chickens immunized with pcDNA3.1/H5-HSP70. This study demonstrated that chickens immunized with HSP70 based H5 DNA vaccine developed higher antibody titer compared to chickens immunized with H5 alone. However, the increase in HI antibody titer was not significantly different (P > 0.05). As expected, the control chickens inoculated with pcDNA3.1/HSP70 and pcDNA3.1 showed no evidence of HI antibody responses. In conclusion, we have demonstrated for the first time that HSP70-based H5 DNA can improve the induction of humoral immune response in chickens and is a promising candidate of DNA vaccine for AIV infection. Further studies are required to explore the role of HSP70 as genetic adjuvant for DNA vaccine in chickens.